Pengaruh Kinerja Keuangan dan Keputusan Investasi Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Intervening - Adrianingtyas, Dea Agustin (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2019)
Abstract. This study aims to prove the effect of financial performance and investment decisions on firm value with dividend policy as an intervening variable. The research method uses a quantitative approach with financial report documentation on chemical sector companies listed on the Indonesia Stock Exchange for the period 2013-2017. Data analysis using classical assumption test and path analysis. The results showed that financial performance has a negative and significant effect on firm value, investment decisions and dividend policy does not affect company value, financial performance and investment decisions have a positive and significant effect on dividend policy, and partially financial performance and investment decisions have an influence on value company with dividend policy as an intervening variable.Â Keywords: financial performance, investment decisions, firm value, dividend policy